Analysis of quantitative trait loci in mice suggests a role of Enoph1 in stress reactivity. (17th November 2013) - Barth, Alexander; Bilkei‐Gorzo, Andras; Drews, Eva; Otte, David M.; Diaz‐Lacava, Amalia; Varadarajulu, Jeeva; Turck, Christoph W.; Wienker, Thomas F.; Zimmer, Andreas
Abstract Significant progress in elucidating the genetic etiology of anxiety and depression has been made during the last decade through a combination of human and animal studies. In this study, we aimed to discover genetic loci linked with anxiety as well as depression in order to reveal new candidate genes. Therefore, we initially tested the behavioral sensitivity of 543 F2 animals derived from an intercross of C57BL/6J and C3H/HeJ mice in paradigms for anxiety and depression. Next, all animals were genotyped with 269 microsatellite markers with a mean distance of 5.56 cM. Finally, a Quantitative Trait Loci (QTL) analysis was carried out, followed by selection of candidate genes. The QTL analysis revealed several new QTL on chromosome 5 with a common core interval of 19 Mb. We further narrowed this interval by comparative genomics to a region of 15 Mb. A database search and gene prioritization revealed Enoph1 as the most significant candidate gene on the prioritization list for anxiety and also for depression fulfilling our selection criteria. The Enoph1 gene, which is involved in polyamine biosynthesis, is differently expressed in parental strains, which have different brain spermidine levels and show distinct anxiety and depression‐related phenotype. Our result suggests a significant role in polyamines in anxiety and depression‐related behaviors. <boxed-text content-type="graphic" id="jnc12517-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Enoph1, an enzyme of the methionine salvage pathway involved in polyamine biosynthesis, was identified by QTL analysis as a candidate gene contributing to stress‐sensitivity in a F2 population of mice derived from C57BL/6J × C3H/HeJ intercrosses. The parental strains express two different protein variants of Enoph1, show different Enoph1 expression levels, and have different brain spermidine levels. These findings suggest that Enoph1 modulates stress sensitivity in these strains.